Why I am not a Christian : and other essays on religion and realted subjects - Russell, Bertrand 1872-1970 (Routledge classics, 2004)
While its tone is playful and frivolous, this book poses tough questions over the nature of religion and belief. Religion provides comfortable responses to the questions that have always beset humankind - why are we here, what is the point of being alive, how ought we to behave? Russell snatches that comfort away, leaving us instead with other, more troublesome alternatives: responsibility, autonomy, self-awareness. He tells us that the time to live is now, the place to live is here, and the way to be happy is to ensure others are happy